Funciones desempeñadas como analista de costos en el área de contabilidad en la empresa inmobiliaria Constructora Galilea S.A.C. - Aranda Asmat, Eddy Christian (2020)
The purpose of this report is to present my work in the Accounting area at Constructora Galilea SAC, during the period from April 2012 to March 2019.The main objective of this report is to establish the importance of cost management and its use as part of the organization's strategy.Identification of inefficient processes and continuous improvement in order to optimize the use of the organization's resources.Based on the planned objectives, the usefulness of cost management as a strategic tool and the establishment of control policies that allow to standardize processes and correctly determine the construction cost to determine the profitability of the organization for decision-making is mainly concluded. from management.On the other hand, within the main recommendations we can mention the requirement of knowledge and management of International Financial Information Standards, in order to correctly apply the treatment of the company's operations; as well as the use of tools of treatment of large volumes of information (big data and data analytics) that contribute to the analysis and knowledge of all the processes of the organization to determine the action strategies and the monitoring of financial planning.